"Regrowth-free" fabrication of high-current-gain AlGaN/GaN heterojunction bipolar transistor with N-p-n configuration. (1st April 2022) - Kumabe, Takeru; Watanabe, Hirotaka; Ando, Yuto; Tanaka, Atsushi; Nitta, Shugo; Honda, Yoshio; Amano, Hiroshi
Abstract: An AlGaN/GaN heterojunction bipolar transistor (HBT) with N-p-n configuration was fabricated by the "regrowth-free" method, resulting in a contamination-free emitter-base AlGaN/GaN heterojunction. The low-bias-power-based low-damage inductively coupled plasma–reactive ion etching was employed in this study for emitter mesa definition instead of the conventional selective-area-regrowth technique. The method successfully minimized the etching-induced damage in the p-GaN base layer and the contamination at the emitter-base AlGaN/GaN heterojunction. Consequently, the fabricated device exhibited a high current gain of 25, the highest current density of 15.0 kA cm −2, and the lowest on-state voltage offset of 0.75 V ever reported for AlGaN/GaN HBTs.